Verses of the Grave and the Realm of Barzah in Tafsir Fathkhul Qadir: Al-Shaukani's Hermeunetics - Maryono, M; Ridwan, Muhammad; Yusyama, Asep Yana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this study is to examine Al-Shaukani's tafsir in terms of Al-Shaukani's hermeneutics in Tafsir Fathkhul Qadir eschatological verses as well as the implications of the theory and implementation of the various categories of tafsir studies. The method of this research uses a descriptive qualitative method, it is found that Al-Shaukani's hermeneutics are applied to verses about the phenomena of the grave and the realm of barzah. The results of this study are the favors and punishments of the grave according to Al-Syauqani's view. The realm of the grave and the realm of barzah is not limited to the tomb, but more broadly wherever there is a body can be acted as the realm of the grave and the realm of barzah, even if it is in the form of ashes or in the belly of a fish. The conclusion of this research produces several findings, including: First, al-Shaukani's hermeneutics was born from the principle of convergence between riwāyah and dirāyah. Viewed from the perspective of the triadic structure in hermeneutics, "riwāyah" represents the authority of the author, while "dirāyah" represents the authority of the text. The convergence of riwāyah and dirāyah makes al-Shaukānī's interpretation refer to inclusive, egalitarian, and retrospective literature. Second, al-Shaukānī applies the principles of hermeneutics consistently to his interpretation of the realm of the grave and the realm of barzah in the Quran. Meanwhile, in terms of the history of hermeneutics, what al-Shaukānī did was not far from the discussions that emerged in classical hermeneutics, namely in the form of interpretation theory, philological methods, or - at most - linguistic methods of understanding.